Iowa RBA, November 23, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for November 23, 1998. Highlights include Clark's Grebe, Black-legged Kittiwake, Black Scoter, and Red Crossbill. Includes notes for updates for November 25. Epson - sheet feed/flatbed